2006
DOI: 10.1242/jcs.03097
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the polarity kinases PAR-1/MARK by 14-3-3 interaction and phosphorylation

Abstract: Members of the PAR-1/MARK kinase family play critical roles in polarity and cell cycle control and are regulated by 14-3-3 scaffolding proteins, as well as the LKB1 tumour suppressor kinase and atypical protein kinase C (PKC). In this study, we initially investigated the mechanism underlying the interaction of mammalian MARK3 with 14-3-3. We demonstrate that 14-3-3 binding to MARK3 is dependent on phosphorylation, and necessitates the phosphate-binding pocket of 14-3-3. We found that interaction with 14-3-3 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 54 publications
4
67
1
4
Order By: Relevance
“…In addition to the SIKs, the MAP/microtubule affinity-regulating kinases (MARKs) subfamily of AMPK related Ser/Thr kinases has also been shown to interact with 14-3-3 proteins [32,44]. Although MARKs have been primarily linked to the regulation of cell polarity, they can also phosphorylate CRTCs and class IIA HDACs [13,14,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the SIKs, the MAP/microtubule affinity-regulating kinases (MARKs) subfamily of AMPK related Ser/Thr kinases has also been shown to interact with 14-3-3 proteins [32,44]. Although MARKs have been primarily linked to the regulation of cell polarity, they can also phosphorylate CRTCs and class IIA HDACs [13,14,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, there appeared another report that one of the family kinases MARK3 is also phosphorylated by aPKC not only on T595 but also on several other residues, which collectively contribute to the regulation of Par1b/MARK2 localization (Goransson et al, 2006). However, there is a common feature in these reports that the localization of Par1b/MARK2 is regulated by phosphorylation from the membrane to the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…For proteins with numerous 14-3-3 binding sites such as MARK2, the peptide array/overlay method can be used to parse out the contributing sites (supplementary Fig. S5) whereas mutational analysis of the complete protein is much more complex and uninformative (29). We also showed that in silico prediction can aid in validating 14-3-3 targets containing at least two binding sequences (supplementary Fig.…”
Section: Discussionmentioning
confidence: 89%
“…S5). The mammalian MARK3 kinase has been extensively mapped for 14-3-3 binding sites, but no key "gatekeeper site" was found (29). Likely MARK2, similar to MARK3, contains multiple 14-3-3 binding sites; of the known phosphorylation sites on MARK3 (29), 5/7 were positive for 14-3-3 binding by peptide overlay.…”
Section: A Widespread Association Of 14-3-3 With [Ps/t]xr Containing mentioning
confidence: 99%
See 1 more Smart Citation